Eksistensi Hukum dalam Hidup Bermasyarakat di Era Digitalisasi - Ardyawati, Atha Hukama; Syahidana, Sahara Islami; Vimala Bulan, Miranda Eryna; Cahayo, Raul Gindo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The digital revolution has created a virtual space that fundamentally transforms social interactions and gives rise to new norms, such as the phenomenon of cancel culture. This rapid dynamic creates a legal vacuum where conventional regulations, like the Information and Electronic Transactions Law (UU ITE), are considered outdated, prone to multiple interpretations, and less effective in responding to cybercrime and personal data protection issues. This article aims to review and reaffirm the existence of formal law as the primary guarantor of order and justice in the digital era. This research was conducted using a normative juridical method, employing a statutory and conceptual approach, to analyze the adaptation of legal rules to the complexity of cyberspace, including challenges of international jurisdiction and the limitations of law enforcement officials. The research results affirm that the existence of law is an absolute necessity realized through adaptive regulation. This is marked by the renewal of the UU ITE and the establishment of the Personal Data Protection Law (UU PDP) as legal milestones in the formalization of digital norms. However, the effectiveness of law in regulating the virtual space is not solely dependent on juridical legal instruments. The success of the law actually lies in a tripartite synergy between legal authority exercised by the state, the improvement of individual digital literacy and ethical awareness, and active supervision initiated by the community. This synergy between law, power, and social norms becomes the essential foundation for building a healthy, inclusive, and just digital space.